Revisiting Bretton woods: Proposals for reforming the international monetary institutions - Raymond F. Mikesell (Levy Economics Institute of Bard College, 1996)
Raymond F. Mikesell outlines the activities of the International Monetary Fund (IMF) and the World Bank over the course of their history and evaluates the organizations' success in meeting their original and subsequent goals. He analyzes the debate over the IMF's role in managing the international monetary system, managing currency crises, and providing credit to newly capitalist countries and examines proposals that the World Bank do more to promote private investment in developing countries, make more loans for expanding social and economic objectives, and improve the efficiency of its operations. Mikesell recommends that (1) the World Bank Group and IMF should be merged to form a single organization, the World Bank and Fund Group (WBFG); (2) neither the IMF nor the WBG should be given responsibility for establishing and managing an exchange rate target zone system or for stabilizing the exchange rates of the major currencies; (3) the establishment of additional institutional constructs to deal with financial crises should be deferred; (4) the WBG should move rapidly to change the composition of its lending by making fewer loans to governments and state enterprises and more loans to the private sector, including nongovernmental, nonprofit entities; and (5) the WBG should be gradually downsized by reducing the number of countries eligible for loans.
Keywords: 330